(untitled) (Herald of the National Children’s Medical Center, 2024)
Hemangiomas of the gastrointestinal tract (GI tract) are extremely rare angiogenesis in pediatric surgery. Predominantly capillary, cavernous and mixed hemangiomas occur in both children and adults. The localization of gastrointestinal hemangiomas varies, they can be single or multiple. Most often, these neoplasms occur in the small intestine, where their frequency is about 5%. According to the literature, hemangiomas are 1.5 times more common in men than in women. At the same time, data on pediatric gastrointestinal hemangiomas are not numerous.